Self-managed working time and employee effort: Theory and evidence - Michael Beckmann; Thomas Cornelissen; Matthias Kräkel (Deutsches Institut für Wirtschaftsforschung (DIW), 2015)
This paper theoretically and empirically examines the impact of self-managed working time (SMWT) on employee effort. As a means of increased worker autonomy, SMWT can theoretically increase effort via intrinsic motivation and reciprocal behaviour, but can lead to a decrease of effort due to a loss of control. Based on German individual-level panel data, we find that SMWT employees exert higher effort levels than employees with fixed working hours. Even after accounting for observed and unobserved characteristics there remains a modest positive effect. This effect is mainly driven by employees who are intrinsically motivated, suggesting that intrinsic motivation is complementary to SMWT. However, reciprocal work intensification does not seem to be an important channel of providing extra effort.
Keywords: J24; J81; M50; 330; self-managed working time; worker autonomy; employee effort; reciprocity; intrinsic motivation; complementarity